Outcomes of early fiberoptic bronchoscopic sputum aspiration and lavage after thoracoscopic and laparoscopic esophageal cancer surgery: a randomized clinical trial - Wu Wang; Jin-biao Xie; Tian-bao Yang; Shi-jie Huang; Bo-yang Chen (Journal of Cardiothoracic Surgery, 2023)
Abstract Background This study aims to investigate the outcomes of patients who received early fiberoptic bronchoscopic sputum aspiration and lavage after thoracoscopic and laparoscopic esophagectomy due to esophageal cancer. Methods A prospective randomized clinical trial was performed between March 2020 and June 2022. Patients who were scheduled for thoracoscopic and laparoscopic esophagectomy due to esophageal cancer were enrolled. Then, these patients were assigned to the control group (traditional postoperative care) and study group (traditional postoperative care with early bronchoscopic sputum aspiration and lavage). The outcomes, which included the length of hospital stay and medical expenses, and postoperative complications, which included pulmonary infection, atelectasis, respiratory dysfunction and anastomotic leakage, were compared between these two groups. Results A total of 106 patients were enrolled for the present study, and 53 patients were assigned for the control and study groups. There were no statistically significant differences in gender, age, and location of the esophageal cancer between the two groups. Furthermore, the length of hospital stay was statistically significantly shorter and the medical expenses were lower during hospitalization in the study group, when compared to the control group (12.3 ± 1.2 vs. 18.8 ± 1.3 days, 5.5 ± 0.9 vs. 7.2 ± 1.2 Chinese Yuan, respectively; all, P < 0.05). Moreover, there were statistically significantly fewer incidences of overall complications in study group, when compared to the control group (20.7% vs.45.2%, P < 0.05). Conclusions For patients with esophageal cancer, early fiberoptic bronchoscopic sputum aspiration and lavage after thoracoscopic and laparoscopic esophagectomy can shorten the length of hospital stay, and lower the medical expense and incidence of postoperative complications.